Faktor-Faktor Yang Mempengaruhi Minat Generasi Z Terhadap Niat Menggunakan Pinjaman Online - Al Rahma, Nabillah Zakia; Wibowo, Purwo Adi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This research aims to analyze the influence of perceived ease of use, perceived usefulness, and social influence on the behavioral intention of Generation Z in Jepara Regency in using online loan services. The population in this study was all Generation Z in Jepara Regency, with a sample size of 100 respondents obtained through random sampling techniques using the Slovin formula. Primary data was collected through questionnaires and analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The research results show that perceived ease of use has a significant effect on Generation Z's behavioral intention in using online loan services with a P value of 0.008. This indicates that the easier a technology is to use, the higher the user's interest in adopting it. Apart from that, perceived usefulness was also proven to have a significant influence with a P value of 0.000, which means that individuals are more likely to use online loan services if they feel clear benefits from using them. On the other hand, social influence has no effect on behavioral intention, as evidenced by the P value of 0.404, which shows that Generation Z's decision to use online loan services is more influenced by individual factors than social pressure.